A Study of Employees’ Turnover Intention among The post-80s and 90s in China - XIE, WENYI (2017)
Abstract With the increasingly fierce competitions in both internal and external market, many Chinese organizations has increasingly realized the importance of the human capitals. So they tried their best to motivate and retain the talented employees. However, the fact is that as the post 80s and 90s employees have played a more and more important role in the labor market over the past decade, the employee turnover rate has become higher and higher. Therefore, one of the reasons why the researcher choose this topic is that the problems of high turnover rates of the post 80s and 90s employees has become a significant problem that needed to be solved, but few academic literature discussed about it. There is a huge gap between the human resource practices and academic areas. So the purpose of this research is to better understand the reasons for the turnover intentions of the post 80s and 90s employees in China from five main dimensions, including compensation and benefits, career development opportunities, training and promotion opportunities, and corporate culture. A closed-ended questionnaire was conducted in this research where about 174 questionnaires have been collected. The results of this research has demonstrated that these five factors are actually negatively related to the turnover intentions of the post 80s and 90s employees(although the findings of this research all shows a positive linear correlation because of the question setting,it will be discussed in the findings part in detail). In the end, the research would also provide some suggestions for Chinese organizations in order to reduce the turnover rates of the post 80s and 90s employees. Key words: Compensation; Career development; Training; Promotions; Organizational culture; Turnover intentions; The post 80s and 90s employees in China